2013
DOI: 10.1021/sc400126h
|View full text |Cite
|
Sign up to set email alerts
|

Nitridated Fibrous Silica (KCC-1) as a Sustainable Solid Base Nanocatalyst

Abstract: We observed that support morphology has dramatic effects on the performance of nitridated silica as a base. By simply replacing conventional silica supports (such as SBA-15 and MCM-41) with fibrous nanosilica (KCC-1), we observed multifold enhancement in the catalytic activity of the nitridated solid base for Knoevenagel condensations and transesterification reactions. This enhancement of the activity can be explained by amine accessibility, which is excellent in KCC-1 due to its open and flexible fibrous stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…The cross-polarization experiment is sensitive to a number of factors (e.g., the rigidity of the silicon-amine sites and 1 H density in the sample and near the silicon-amine site), so a quantitative estimate of the ratio of different silicon-amine sites could not be obtained. For SBA-15-N900 and SBA-15-N1200, we directly confirmed the presence of secondary and tertiary amines using 1 H-detected 15 N-1 H correlation spectra at the natural 15 N abundance. Figure 2 shows that SBA-15-N900 predominantly has secondary amines present while SBA-15-N1200 has a high tertiary amine content.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The cross-polarization experiment is sensitive to a number of factors (e.g., the rigidity of the silicon-amine sites and 1 H density in the sample and near the silicon-amine site), so a quantitative estimate of the ratio of different silicon-amine sites could not be obtained. For SBA-15-N900 and SBA-15-N1200, we directly confirmed the presence of secondary and tertiary amines using 1 H-detected 15 N-1 H correlation spectra at the natural 15 N abundance. Figure 2 shows that SBA-15-N900 predominantly has secondary amines present while SBA-15-N1200 has a high tertiary amine content.…”
mentioning
confidence: 66%
“…Figure 2 shows that SBA-15-N900 predominantly has secondary amines present while SBA-15-N1200 has a high tertiary amine content. The corresponding 15 N-1 H correlation spectra could not be obtained for SBA-15-N500 and SBA-15-N700 because of their low nitrogen content. It is to be expected that the variation in peak position and intensity for the CP experiments (Figure 1 A-E 1 H should be seen.…”
mentioning
confidence: 99%
“…The results showed that high catalytic activity was due to the highly accessible KCC-1 support while excellent stability was probably due to the fibrous nature of the support. Additionally, Bouhrara et al studied the use of nitridated fibrous silica (KCC-1) for Knoevenagel condensations and transesterification reactions[56]. The high reaction activity was due to the fibrous morphology with the highly accessibility of basic and acidic sites.Contemporaneously, Peng et al reported a center radially fibrous silica encapsulated TS-1 zeolite (TS-1@KCC-1) with enhanced hydrothermal and mechanical stability for one-pot synthesis of benzamide[57].…”
mentioning
confidence: 99%
“…The condensation reaction is generally performed by using stoichiometric or catalytic amounts of ammonia, primary and secondary amines, pyridine, piperadine 6 dimethylamino 7-10 Al 2 O 3 11 , SmI 3 12 , CdCl 2 13 , LaCl 3 14 , ZnCl 2 15 , Zeolite 16 , ZnCl 4 -SiO 2 17 , fluorapatite 18 , hydroxyapatite 19 , metal oxides 20 23 , hydrotalcite in ionic liquids 24 , mesoporous organosilica supported potassium carbonate (BPMO-IL-KCO 3 ) 25 , UiO-66-NH 2 26 . In addition, there are certain reports on the use of electrochemical induced, microwave and ultra sound irradiation methods for Knoevenagel condensation [27][28] 32 , amine functionalized PAN 33 , Pd(0) 34 has been repor ted to catalyze the Knoevenagel condensation reaction. Various MOF [35][36][37] has also been tried to catalyze the above reaction.…”
mentioning
confidence: 99%